Pencegahan Tindak Pidana Kolusi dan Nepotisme Guna Menegakkan Supremasi Hukum di Indonesia - Raden Joa Kansha Ramadhan Ladar Sirair; Sasmini Sasmini (Fakultas Hukum, Universitas Warmadewa, 2024)
Corruption is a serious crime that threatens national stability, the economy, democracy, and the rule of law. In Indonesia, weak enforcement of Law No. 28 of 1999 hampers anti-corruption efforts. Collusion and nepotism, driven by the abuse of power for personal or group interests, further exacerbate corruption. This study analyzes the law’s effectiveness in addressing these issues and formulates optimal prevention strategies. Using a normative legal approach and literature study, the findings reveal that weak law enforcement, inadequate oversight, and lenient sanctions contribute to high corruption levels. Strengthening law enforcement, improving oversight mechanisms, and imposing stricter sanctions are essential policy reforms. By enhancing legal frameworks and enforcement strategies, collusion and nepotism can be mitigated, strengthening Indonesia’s anti-corruption efforts. A more robust legal system will foster transparency, accountability, and good governance, ultimately reducing corruption and promoting national stability.